COMPUTATIONAL INSIGHTS INTO NATURAL BIOACTIVE COMPOUNDS INTERACTING WITH MOSQUITO PROTEINS - N B Geetha,; S E Sangeetha,; Devasena B,; L Ashwini,; Nafisa Farheen,; Mahalakshmi J, (The Bioscan, 2025)
Mosquito control programs have traditionally relied on synthetic pesticides, which pose significant risks to the environment and non-target organisms. In response to these concerns, naturally derived plant compounds have emerged as promising alternatives due to their eco-friendly and target-specific nature. Recent research has increasingly focused on using protein inhibitor strategies to manage insect pests by targeting their digestive enzymes.This review highlights the potential of using in silico techniques, particularly molecular docking and molecular dynamics simulations, to evaluate the interaction between mosquito gut proteases and naturally occurring protein inhibitors. These computational approaches allow for the prediction and assessment of ligand–protein interactions, facilitating the identification of potent inhibitor candidates. Such analyses can significantly streamline the development of novel biopesticides and transgenic approaches by reducing the cost and time associated with traditional in vitro testing.By providing insights into the structural compatibility and binding affinity of natural compounds with mosquito proteins, in silico methods serve as valuable tools for the sustainable and strategic control of mosquito populations.